Analytical study of the dimensional stability of tropical brazilian wood species - Almeida, Tiago Hendrigo; Almeida, Diego Henrique; de Moura Aquino, Vinicius Borges [UNESP]; Christoforo, André Luis; Lahr, Francisco Antonio Rocco (Universidade Federal de Santa Maria, 2023)
Brazil owns a large vegetal covering and the best utilization of these materials requires physical and mechanical characterization procedures. Equations found in the literature make easier the wood properties determination. At this context, well known authors developed the equation βl = βt / 23, being βl and βt the longitudinal and tangential shrinkage percentages, for βl estimation based on the βt value specially for wood species from the Northern hemisphere. This paper aims to investigate the accuracy of this equation for fifteen tropical Brazilian wood species covering the entire range of hardwood strength classes according to the Brazilian Normative ABNT NBR7190. The average experimental values of βl and βt were 7.71% (CV = 26,71%) and 0.73% (CV = 38,76%), respectively. The non-parametric KruskalWallis ANOVA refuted the hypothesis of equivalence between theoretical and experimental βl values (p-value = 0.0000). A linear regression model fitted to experimental values provided βl = βt / 9,84 as optimal solution (p-value = 0.0000, R2 = 47,23%). According to results it is possible to conclude that the value of longitudinal shrinkage percentage of tropical Brazilian wood species is statistically 2,34 times greater than the value found in the literature, which impacts the design of timber structures procedures increasing the internal stresses in timber structural elements.
Estudo analítico da estabilidade dimensional longitudinal das espécies de madeira tropicais brasileiras
Keywords: Longitudinal shrinkage; Tangential shrinkage; Tropical Brazilian wood